Studi Deskriptif Kualitas Hidup Mahasiswa FK UNTAR 2022 yang Mengalami Gangguan Hidung dan Sinus Paranasal - Nayila Salsabila; Mira Amaliah (Pusat Riset dan Inovasi Nasional, 2026)
Background: Rhinosinusitis is an inflammatory condition of the nasal cavity and paranasal sinuses. It can be caused by various factors such as infection (bacterial, viral and fungal infection), allergic conditions, and anatomical obstructions of the nasal and sinuses passage. This condition can occur across all age groups and has a relatively high global prevalence. It is often chronic or recurrent that potentially lowering the quality of life of affected individual. Common symptoms include nasal congestion, nasal discharge, facial pain or pressure, olfactory disturbances, and facial discomfort, which may interfere with daily activities among university students. Objective: To assess the quality of life of medical students experiencing nasal and paranasal sinuses disorder at the Faculty of Medicine Tarumanagara University class of 2022. Method: This was a descriptive cross-sectional study with number of sample consisted of 145 students from class of 2022 who met the inclusion criteria. This study used Rhinosinusitis Disability Index (RSDI) questionnaire to measure the quality of life. Data were analyzed descriptively and presented in tables. Results: The majority of the respondents were female (78,6%) and mean age was 20,48 years. The most commonly reported symptom was nasal congestion (93,8%). Most samples had a good quality of life (57,90%). Conclusion: This study reported a good quality of life among students of Faculty of Medicine Tarumanagara University class of 2022 who had suffered from nasal and paranasal sinuses disorder.